The Role of the Anti-Corruption Commission Supervisory Board in Institutionalizing Accountability - Reza Octavia Kusumaningtyas; Ong Argo Victoria (Lembaga Contrarius Indonesia, 2025)
The Supervisory Board of Indonesia’s Corruption Eradication Commission (KPK) holds significant potential to strengthen ethical standards and prevent the abuse of power. However, its effectiveness remains hindered by persistent issues, particularly concerning its independence, transparency, and vulnerability to political interference. This study aims to evaluate the role of the Supervisory Board in institutionalizing accountability and compares its framework with the supervisory model adopted by the Malaysian Anti-Corruption Commission (MACC), which is known for its inclusive and multi-layered oversight structure. Employing a normative legal research method, this study integrates a qualitative approach, comparative legal analysis, review of relevant literature, and a case study of the MACC’s supervisory system. The findings reveal that Malaysia’s model, which incorporates multiple independent oversight bodies and encourages public participation, promotes stronger accountability and transparency. In contrast, the centralized nature of the KPK Supervisory Board, which places significant control within the executive branch, raises concerns over potential political intervention and conflicts of interest. The study concludes that to function effectively as a credible accountability mechanism, the KPK Supervisory Board requires institutional reform. Enhancing its structural independence and transparency is essential to ensuring its role in the sustainable fight against corruption in Indonesia.